Hepatitis C Virus Frequency in Hemodialysis Patients at A Tertiary Care Facility in Rawalpindi, Northern Pakistan - Rathore, Muhammad Ali; Saqi, Muhammad Khaleeq; Ghani, Eijaz; Niazi, Saifullah Khan; ahmed, faraz; Hammad, Hina (Pakistan Armed Forces Medical Journal, 2024)
Objective: To detect the frequency of anti-HCV antibodies in hemodialysis patients.Study Design: Cross-sectional study.Place and Duration of Study: Department of Virology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jul to Dec 2021.Methodology: One hundred and fifteen patients were selected from the Hemodialysis Centre. Blood samples were taken from patients undergoing hemodialysis to detect anti-HCV by enzyme-linked immunosorbent assay. The samples were spun up and checked for anti-HCV antibodies using the Bio-Rad Monolisa anti-HCV version 3 kit and a 3rd generation ELISA.Results: A total of 115 patients were tested for anti-HCV. The anti-HCVs in this study were detected in 34(29.56%) patients. The mean duration of hemodialysis was 2.3±1.4 years. Out of 115 patients, 81(70.4%) had no significant history. Of the 34 positive patients, 15(44.2%) had a history of intravascular exposures, 12(35%) had a history of blood transfusion, 3(8.8%) had a history of tooth extraction surgery during the dialysis period, and 4(11%) had a history of minor surgery during dialysis.Conclusion: The study emphasizes the significant frequency of HCV infection in hemodialysis patients, particularly those with a history of intravenous exposure and blood transfusions.